Dispersive micro-solid-phase extraction of dopamine, epinephrine and norepinephrine from biological samples based on green deep eutectic solvents and Fe3O4@MIL-100 (Fe) core–shell nanoparticles grafted with pyrocatechol1. Issue 80 (2nd September 2015) - Khezeli, T.; Daneshfar, A.
<x xml:space="preserve">Abstract</x> DA, EP and NE were determined without interference of ascorbic acid using grafted Fe3O4@MIL-100 (Fe) NPs and a green solvent.